(untitled) (Eurasian Journal of Philology Science and Education, 2016)
Combining science and humanitarian clusters of special educational programs within the elective course seems to be one of the most promising innovative techniques that can harmonize and significantly expand the professional competencies of graduates. The integrative approach in this case regard the study of language and literature in the aspect adopted Programme «Cultural Heritage» in the country, initiated by the President of Kazakhstan N. A. Nazarbayev and carried out by specialists of different industries and activities With this purpose in the educational program of a number of humanitarian and natural faculties of Al-Farabi Kazakh National University introduced an elective course «Kazakh language and literature», the aim of which is related to the direct needs and challenges of today. One of the priorities of the discipline is to acquire knowledge of international experience on environmental issues of cultural heritage. The base foundation course program is based on sections on the totality of the material and spiritual cultural achievements, the national heritage of the Kazakh people, first of all – the oral poetic tradition.